2009
DOI: 10.1179/174328408x353741
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal stability of novel amorphous Al70Fe25Zr5 alloy prepared by mechanical alloying

Abstract: A novel amorphous Al70Fe25Zr5 alloy was synthesised through high energy ball milling the mixtures of Al, Fe and Zr powder with the milling intensity of 150G (G is the gravitational acceleration). By comparing with the binary Al–Fe amorphous, differential scanning calorimeter results indicated the crystalline temperature of ternary Al70Fe25Zr5 amorphous alloy shifts higher temperature, and it showed two stages of crystalline reactions which corresponded to the formation of Al5Fe2 and Al3Zr phases respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Especially, the analysis of the XRD pattern of Al-Zr has shown that there are two typical broad diffuse diffraction peaks, the pre-peak diffuse maxima at 32.4° and the main diffuse maxima at 41.0°. This finding can be inferred in the Al-Zr amorphous alloys [20]. Appearance of a shoulder or developing asymmetry of the main diffuse maxima indicates that the amorphous alloys contains the areas with different shortest interatomic distances [23], as apparently form different types of amorphous structure.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Especially, the analysis of the XRD pattern of Al-Zr has shown that there are two typical broad diffuse diffraction peaks, the pre-peak diffuse maxima at 32.4° and the main diffuse maxima at 41.0°. This finding can be inferred in the Al-Zr amorphous alloys [20]. Appearance of a shoulder or developing asymmetry of the main diffuse maxima indicates that the amorphous alloys contains the areas with different shortest interatomic distances [23], as apparently form different types of amorphous structure.…”
Section: Resultsmentioning
confidence: 68%
“…The GFA of Al-base base alloys can be improved by addition of Zr, Nb, Ni and other elements [15][16][17][18][19][20][21]. Bo Zhu et al analyzed the addition of V, Fe and Cu to amorphous Albase alloy and found that the GFA of Al75V12.5Fe12.5-XCuX increased with the decrease of Cu content due to the positive mixing enthalpies of V-Cu (+5kJ/mol) and Fe-Cu (+13 kJ/mol) [21].…”
Section: Introductionmentioning
confidence: 99%
“…During MA process, solid state reactions would happen between two or more blended elemental powders, resulting in the fragmentation and plastic deformation of particles. With the repeated diffusion, cold welding and fracture of powders, a composite coating could be formed and bonded with target alloys [14][15][16][17][18]. In comparison with other methods, MA process is more attractive due to its low cast, simplicity and high production.…”
Section: Introductionmentioning
confidence: 99%
“…22 Several changes, such as the alloying, chemical interaction, diffusion, cold welding and formation of new phases, could take place at the interface between the target and the coating particles at ambient temperature. [23][24][25][26][27][28] Furthermore, it is possible to make alloys from normally immiscible components due to the repeated fracture and cold welding of the constituent powder particles. 29 Therefore, this proposed method possesses several attractive features that may enable its use in many practical applications.…”
Section: Introductionmentioning
confidence: 99%